ONA VA FARZAND MUNOSABATLARI О‘ZBEK PSIXOLOGLARINING TADQIQOT OB`YEKTI SIFATIDA - Abdullayeva, D.U. (SCIENCE and SOCIETY, 2023)
In this article, the work of Uzbek psychologists on the uniqueness of mother-child relations in the family, the impact of these relations on family strength and children's education is analyzed in detail.
Keywords: family; upbringing; interpersonal relationship; dysfunctional family; child upbringing; family upbringing; communication; attitude; psychological environment; ethnopsychological characteristic